The increased level of Tspan5 in villi suggests more proliferation and invasiveness of trophoblasts in tubal pregnancy. (September 2018) - Gao, Tianyang; Liang, Yingqiu; Tang, Haiyu; Quan, Li
Abstract: Objective: This study was to determinate the expression of Tspan5 in tubal ectopic implantation sites and to explore the correlation of the expressive level of Tspan5 at maternal-fetal interface and the occurrence of tubal ectopic pregnancy. Study Design: This is a retrospective study. Trophoblastic and endometrial tissues were collected from tubal ectopic pregnancy(Total of 40), and intrauterine pregnancy(Total of 41), who had voluntary abortion, non-pregnancy women(Total of 12), who recieved an diagnostic uterine curettage before IVF-ET for male infertility. All samples were collected from women aged 23–40 years, from February 2012 to January 2014. Results 1. In human villi Tspan5 was primarily located in cytoplasm and on the surfaces of cytotroblasts(CTs) and extravillous trophoblast(EVCTs). The intensity of Tspan5 in tubal pregnancy was significantly higher than that in normal intrauterine pregnancy, showing significant differences (Mean of IOD:109.39 ± 61.84 Vs. 89.04 ± 36.44;t = 2.33, P  = 0.023). 2. In human deciduas of intrauterine pregnancy or endometrium of tubal pregnancy and non-pregnancy Tspan5 expressed in cytoplasm and membrane of glandular epithelial cells. The expressive level of this protein was increased in tubal pregnancy than that in intrauterine pregnancy and non-pregnancy(Mean of IOD:144.18 ± 106.22 Vs. 93.43 ± 67.10, P  = 0.037; 144.18 ± 106.22 Vs. 88.56 ± 33.24, P  = 0.018). Conclusion: Our study indicated that the trophoblasts in tubal pregnancy showed more proliferative and invasive characteristics. Dysregulation of Tspan5 in decidual microenvironment may relate to the retention of embryo in fallopian tube. Support: This study was Supported by Science and Technology Planning Project of Guangdong Province.